2017
DOI: 10.1016/j.expneurol.2017.08.002
|View full text |Cite
|
Sign up to set email alerts
|

HSPB1 mutations causing hereditary neuropathy in humans disrupt non-cell autonomous protection of motor neurons

Abstract: Heat shock protein beta-1 (HSPB1), is a ubiquitously expressed, multifunctional protein chaperone. Mutations in HSPB1 result in the development of a late-onset, distal hereditary motor neuropathy type II (dHMN) and axonal Charcot-Marie Tooth disease with sensory involvement (CMT2F). The functional consequences of HSPB1 mutations associated with hereditary neuropathy are unknown. HSPB1 also displays neuroprotective properties in many neuronal disease models, including the motor neuron disease amyotrophic latera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 81 publications
0
16
0
Order By: Relevance
“…Similarly, overexpression of HSPB1 wild type in astrocytes co-cultured with SOD1(G93A) motor neurons was sufficient to attenuate astrocyte-mediated cytotoxicity. However, CMT2/dHMN-associated mutants of HSPB1 (G84R and R136W) failed to provide this non-cell-autonomous protective function (Heilman et al 2017). It requires pointing out though that the R136W mutant was shown to have an overall increased chaperone activity (Almeida-Souza et al 2010;Almeida-Souza et al 2011).…”
Section: Als-sod1mentioning
confidence: 97%
“…Similarly, overexpression of HSPB1 wild type in astrocytes co-cultured with SOD1(G93A) motor neurons was sufficient to attenuate astrocyte-mediated cytotoxicity. However, CMT2/dHMN-associated mutants of HSPB1 (G84R and R136W) failed to provide this non-cell-autonomous protective function (Heilman et al 2017). It requires pointing out though that the R136W mutant was shown to have an overall increased chaperone activity (Almeida-Souza et al 2010;Almeida-Souza et al 2011).…”
Section: Als-sod1mentioning
confidence: 97%
“…The lack of an overt phenotype in HSPB1-deficient mice [363] suggests that the pathomechanisms of dominant HSPB1 mutations involves a gain-of-function component [352]. However, the loss of cytoprotection is another potential consequence of HSPB1 mutations, which may contribute to the pathomechanism in combination with dominant toxicity [364]. Impaired tolerance to thermal and unfolded protein stress has been observed in patient fibroblasts [365].…”
Section: Downstream Pathomechanismsmentioning
confidence: 99%
“…HSPB1 was shown to protect cells from ER-stress-induced apoptosis by facilitating the proteasomal turnover of BIM, and several disease mutants are defective in this respect [322]. Recent research has demonstrated as well that non-cell autonomous protective effects may be altered by the mutations: while wild-type HSPB1 expressed in astrocytes with SOD1 p.G93A protects co-cultured motoneurons from mutant SOD1 toxicity, the p.G84R and p.R136W fail to show such a protective effect [364].…”
Section: Downstream Pathomechanismsmentioning
confidence: 99%
“…In vitro experiments also support this hypothesis, since both αB-crystallin and HSPB1 overexpression are able to suppress SOD1 aggregation (Yerbury et al, 2013). Focusing on HSPB1, its role in ALS is rather controversial; for example, HSPB1 overexpression is beneficial when tested in different SOD1-based ALS cell models (Patel et al, 2005; Krishnan et al, 2006; An et al, 2009; Yerbury et al, 2013; Heilman et al, 2017), but animal model experiments did not confirm this protective role. In its work, Krishnan et al (2008) showed that the ubiquitous over-expression of human HSPB1 in SOD1-G93A mice [double transgenic SOD1(G93A)/hHSPB1 mice] did not affect disease duration, progression, motor neuron degeneration or SOD1 aggregation, although hHSPB1 overexpression alone (single transgenic hHSPB1 mice) protected against spinal cord ischemia (Krishnan et al, 2008).…”
Section: The Role Of Hspb8 In the Selection Of The Proper Degradativementioning
confidence: 99%